2021
DOI: 10.1038/s41598-021-96393-6
|View full text |Cite
|
Sign up to set email alerts
|

Handwashing knowledge, attitudes, and practices during the COVID-19 pandemic in Saudi Arabia: A non-representative cross-sectional study

Abstract: Handwashing (HW) with water and soap is one of the cheapest and most effective ways of protecting oneself and others against the coronavirus. Here, the HW knowledge, attitudes, and practices of Saudi adults were assessed during the COVID-19 pandemic using a cross-sectional study conducted between May 8 and June 8, 2020, during a partial lockdown period. A web-based validated questionnaire was distributed through different social media platforms, and the sociodemographic characteristics of the participants, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…Participants who had a monthly family income lower than 10,000 THB or 10,000–30,000 THB had less accurate knowledge than those with a monthly family income higher than 30,000 THB. Similarly, Al-Wutayd et al found more accurate knowledge among people with higher incomes ( 46 ). The current findings indicated that social media users had more accurate knowledge than those who never used social media.…”
Section: Discussionmentioning
confidence: 91%
“…Participants who had a monthly family income lower than 10,000 THB or 10,000–30,000 THB had less accurate knowledge than those with a monthly family income higher than 30,000 THB. Similarly, Al-Wutayd et al found more accurate knowledge among people with higher incomes ( 46 ). The current findings indicated that social media users had more accurate knowledge than those who never used social media.…”
Section: Discussionmentioning
confidence: 91%
“…A study in Iran also revealed a positive attitude towards hand washing and avoiding crowded places by the participants as a preventive measure against contracting COVID-19 (Taghrir et al, 2020). Similarly, the majority of respondents in studies conducted in Saudi Arabia (Al-Wutayd et al, 2021), Italy (Scampoli et al, 2021), and the Philippines (Lau et al, 2020), indicated that washing hands and avoiding crowded places are important COVID-19 preventive measures.…”
Section: Discussionmentioning
confidence: 95%
“…Compliance with personal protective equipment standards was higher than with hand hygiene practices. Al-Wutayd/ Aug 2021 91 Handwashing knowledge, attitudes, and practices during the COVID-19 pandemic in Saudi Arabia: A non-representative cross-sectional study 1323 adults Online questionnaire on social media Handwashing knowledge was associated with positive attitudes toward this practice in Saudi adults during the COVID-19 lockdown. Alotaibi/ Aug 2021 92 The Extent of Commitment of Saudis During Holy Ramadan to Social Distancing Measures Required for the Prevention of Transmission of COVID-19.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“… 126 The Saudi Arabian Ministry of Health (MOH) has performed an exhaustive awareness campaign communicated via its website ( https://www.moh.gov.sa/en/awarenessplateform/ ) or direct public awareness sessions, national television programs, several platforms of social media, and mobile phone SMS messages. 91 In collaboration with the “Saudi Center for Disease Control”, the MOH has launched a COVID-19-related guide and health education in more than ten languages to provide all citizens, Saudi and non-Saudi ones, with scientific facts and preventive measurements. This early engagement of the public in prevention/control measures, and the efforts paid to combat claims/misinformation, have been greatly extended.…”
Section: Covid-19 Is a Public Health Emergencymentioning
confidence: 99%